2019
DOI: 10.3390/s19235108
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Optimization from Two Virtual Physical Force Algorithms for Dynamic Node Deployment in WSN Applications

Abstract: With the rapid development of unmanned aerial vehicle in space exploration and national defense, large-scale wireless sensor network (WSN) became an important and effective technology. It may require highly accurate locating for the nodes in some real applications. The dynamic node topology control of a large-scale WSN in an unmanned region becomes a hot research topic recently, which helps improve the system connectivity and coverage. In this paper, a hybrid optimization based on two different virtual force a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Yu et al [ 22 ] reported a novel VF model based on virtual spring force (VFA-SF) and examined the associated efficiency in detail using statistical analysis. To place the self-consistent nodes in large-scale WSNs, a hybrid optimization algorithm based on two separate VF algorithms inspired by the interactions among physical sensor nodes was presented in [ 23 ]. Afterward, a method based on a 3D VF model driven by self-adaptive deployment (named 3DVFSD) was proposed in [ 24 ].…”
Section: Related Workmentioning
confidence: 99%
“…Yu et al [ 22 ] reported a novel VF model based on virtual spring force (VFA-SF) and examined the associated efficiency in detail using statistical analysis. To place the self-consistent nodes in large-scale WSNs, a hybrid optimization algorithm based on two separate VF algorithms inspired by the interactions among physical sensor nodes was presented in [ 23 ]. Afterward, a method based on a 3D VF model driven by self-adaptive deployment (named 3DVFSD) was proposed in [ 24 ].…”
Section: Related Workmentioning
confidence: 99%
“…As shown in Figure 6 , compared with the methods designed for large-scale WSNs, such as the virtual force algorithm inspired by Lennard Jones potential (VFA_LJ) and the virtual force algorithm inspired by Dusty Plasma crystallization (VFA_DP) [ 25 ], the topology produced by the FR-HEX algorithm is obviously more regular in different scale ( and ). VFA_LJ always has some regions with uneven nodes.…”
Section: Simulation Analysis Of Fr-hex Algorithmmentioning
confidence: 99%
“…As shown in the Figure 9 a, to achieve the densest coverage between nodes, the relationship between the distance and the sensing radius of the sensor is [ 25 ]. According to the statistics in the table, for large-scale deployment, the is about .…”
Section: Simulation Analysis Of Fr-hex Algorithmmentioning
confidence: 99%
“…Analytic hierarchy process is more suitable for decisionmaking problems with hierarchical and staggered evaluation indexes, and the target value is difficult to describe quantitatively [4].…”
Section: Introductionmentioning
confidence: 99%